DIGITALISASI SASTRA LISAN LEGENDA GAJAH PUTEH DI TANAH GAYO, ACEH TENGAH MELALUI KOMIK DIGITAL - Agustina, Silvia (IdeBahasa, 2022)
This study raises the urgency of preserving regional literature, especially thelegend of the "Gajah Puteh" from Central Aceh which is starting to be forgottenand has received less attention. With the decline in interest in this literarywork, it is important for researchers to maintain the sustainability andexistence of this cultural heritage. The main objective of the study is to utilizethe digitalization of literature to revive the legend of the "White Elephant" andincrease public appreciation of regional literature. Through a digitalizationapproach, this study aims to create output in the form of digital comics as aninteresting and accessible media for the younger generation, as well as thegeneral public. Digital comics were chosen as a tool to convey the legend in amore interesting and relevant way in a modern context. Thus, it is hoped thatdigital comics can be an effective means of reintroducing the legend of the"Gajah Puteh" to the public, especially in Tanah Gayo, and to arouse interest inlocal literature.Keywords: The Legend of the "Gajah Puteh", moral, digitalization.